Implementasi Sosialisasi Peraturan Pemerintah No. 23 Tahun 2018 Bagi Pelaku Usaha Mikro, Kecil dan Menengah (UMKM) - Hendri, Hendri (Jurnal Vokasi Indonesia, 2018)
Micro, Small and Medium Enterprises which have developed so rapidly from year to year have created tax obligations for these business actors. To help the government MSME Taxpayers in 2013 have issued Government Regulation (PP) number 46. After several years of implementation the government has now issued improvements to the regulation by issuing PP No. 23 of 2018. This regulation was issued to provide tariff relief for MSME business actors. However, the PP that was passed in mid 2018 was felt to still lack socialization to taxpayers. This study focuses on understanding the taxpayers regarding the implementation of these rules. This study concluded that the implementation of the socialization that had been carried out by the government in this case the KPP had not been maximized. Taxpayers do not understand the procedure for determining the time period for imposing a tariff. Taxpayers who are included in the criteria that have certain gross circulation also do not know much about the technical implementation of this PP 23 of 2018.